Cognitive Restructuring Techniques for High School Students' Academic Anxiety: A Literature Review - Maulidina Azza Nabila; Najlatun Naqiyah (Biblio Couns : Jurnal Kajian Konseling dan Pendidikan, 2021)
Academic anxiety is a feeling of anxiety, fear, and a situation are threatening or dangerous, and caused the disruption of thought patterns and physical or behavioral responses to students' academic activities. The purpose of research is to examine and describes the cognitive restructuring techniques to academic anxiety of the secondary school students. The method has used in this research is literature study. The data technique in this research is documentation technique. And also, the data analysis technique has used is content analysis techniques. The results of research are the research, and descriptions of evaluation, monitoring, scope or objectives, as well as suggestions or recommendations for cognitive restructuring techniques to academic anxiety of the secondary school students. From the things has been done, it can be shown that cognitive restructuring techniques are successful in overcoming the academic anxiety of the secondary school students so that cognitive restructuring techniques can be one of the techniques applied to overcome academic anxiety.